ANALISIS DESKRIPTIF ATAS KERTAS KERJA PENYUSUNAN LAPORAN KEUANGAN FISKAL OLEH KANTOR AKUNTAN PUBLIK “X” - Arry Irawan; Setiawan Setiawan; Fiesty Utami (Jurusan Akuntansi Politeknik Negeri Bandung, 2017)
Abstract: This study aims to obtain a valid and reliable knowledge on how the Public Accounting Firm prepares fiscal financial statements by using worksheet. This research uses descriptive qualitative method that is method which aims to describe and explain data or events with qualitative explanation sentences. The qualitative research method emphasizes on observational research methods in the field. In calculating corporate tax payable, corporate income statement is needed to calculate how much earnings before taxes obtained by the company in the current year. After that, we can calculate the company’s income tax payable. However, there are some differences between commercial income statement and the fiscal loss statement. So that a fiscal reconciliation is required. The fiscal reconciliation is made to make the commercial income statement in accordance with the provisions for taxation. So, it would be accepted as an income statement which is in accordance with tax rules and then it can be used for calculating income tax. Keywords: Worksheet, Public Finance Report, Public Accounting FirmAbstract:This study aims to obtain a valid and reliable knowledge on how the Public Accounting Firm prepares fiscal financial statements by using worksheet. This research uses descriptive qualitative method that is method which aims to describe and explain data or events with qualitative explanation sentences. The qualitative research method emphasizes on observational research methods in the field. In calculating corporate tax payable, corporate income statement is needed to calculate how much earnings before taxes obtained by the company in the current year. After that, we can calculate the company’s income tax payable. However, there are some differences between commercial income statement and the fiscal loss statement. So that a fiscal reconciliation is required.The fiscal reconciliation is made to make the commercial income statement in accordance with the provisions for taxation. So, it would be accepted as an income statement which is in accordance with tax rules and then it can be used for calculating income tax. Keywords:Worksheet, Public Finance Report, Public Accounting Firm